2021
DOI: 10.3390/ijerph182111268
|View full text |Cite
|
Sign up to set email alerts
|

More Land, Less Pollution? How Land Transfer Affects Fertilizer Application

Abstract: Reducing fertilizer use is key to curbing agricultural pollution and ensuring food safety. Land transfer enables farmers to obtain a more appropriate production scale, but its effect on the intensity of fertilizer application is not theoretically certain. On one hand, farmers with more land may adopt more scientific production methods, thus reducing the use of chemical fertilizers. On the other hand, the short-term behavior of land grantees on transferred land may increase fertilizer use intensity. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Agricultural subsidy is an incentive guarantee for households to engage in agricultural production activities [ 45 ]. Table 4 demonstrates that land inflow contributes 6% or more to household income than land outflow, as household inflow of land expands the scale of household cultivation [ 28 ]. Households then increase production efficiency through continuous mechanized production, which in turn reduces the cost of agricultural production.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural subsidy is an incentive guarantee for households to engage in agricultural production activities [ 45 ]. Table 4 demonstrates that land inflow contributes 6% or more to household income than land outflow, as household inflow of land expands the scale of household cultivation [ 28 ]. Households then increase production efficiency through continuous mechanized production, which in turn reduces the cost of agricultural production.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Since the existence is usually ensured by activities out of the farm and the maintenance of farming is of secondary importance from economic aspects, so family ideas and farm works factors have a great influence on family behavioral decisions [ 26 ]. Factors such as the degree of land fragmentation, mechanised use and economic development of the village all have a significant impact on the decision to transfer land by farming households [ 27 , 28 ]. In addition, household labour force structure and households with public officials have the advantage of capturing information about transactions, thus increasing the opportunities of land transaction [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the monitoring data of Chinese family farms in 2018, large-scale farmers managed an average of 15 scattered plots, and some farmers even managed as many as 1269 scattered plots [ 54 ]. Farmland fragmentation helped to reduce PM 2.5 [ 29 ].…”
Section: Literature Review and Research Hypotheses Constructionmentioning
confidence: 99%
“…Farmers with large farms are the main force in China’s future use of organic fertilizers, as they can pursue greater long-term agricultural benefits in this way [ 28 ]. Under the condition of reducing the number of applied chemical fertilizers, large-scale land management will not lead to a decline in output [ 29 ]. Meanwhile, for every 1% increase in farm scale, fertilizer use efficiency increases by 0.2%, reducing the environmental pollution caused by excessive use of chemical fertilizers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qiao and Huang (2021), in a study of 306 cotton farmers in China, also found that the risk preference had a negative effect on fertilizer application intensity when the likelihood of fertilizer application achieving the desired effect was high, and a positive effect on fertilizer application intensity when the likelihood of achieving the desired effect was low. Regarding the effect of farmers' operation characteristics on fertilizer application, most studies found that operation scale had a negative effect on fertilizer application intensity (Guo et al, 2018;Wu et al, 2021) and a positive effect on fertilizer utilization efficiency (Zhu et al, 2022). A study by Wu et al (2021) on data from fixed observation sites in rural China found that expanding the operation scale by land transfer had a significantly negative effect on food crop cultivation and farmers' fertilizer application intensity in northwest of China.…”
Section: Literature Reviewmentioning
confidence: 99%